MOLECULAR DYNAMICS SIMULATION OF COHESIVE ENERGIES AND ITS CORRESPONDING LATTICE PARAMETER OF SOME NANOCRYSTALS (FUDMA JOURNAL OF SCIENCES, 2022)
Bulk solids have a microstructure that differs significantly from nanoscale materials. In modern era, new devices are always produced at nano-scale level and existing ones are quantized to fit the global demand. To achieve this, there is a need to understand the behaviour of materials at atomic level. As a result, examining the properties of nanoparticles can help in understanding the nature of small-scale material behavior. The cohesive energy and lattice constant are essential physical quantities that can be used to predict other material properties. In this research, the equilibrium cohesive energies and its corresponding lattice constants of three nanosized crystals (Al, Cu and Ni), were investigated using molecular dynamics simulation method with a semi-empirical embedded atom model (EAM) potential function. The simulated results reveal that the three nanocrystals’ lattice constant match the experimental data. Besides, Al, Cu and Ni have cohesive energies of -3.40 eV, -3.55 eV, -4.44 eV respectively. Cu’s cohesive energy differs from experimental data unlike Al and Ni. The findings in the current research are in good agreement with those obtained utilizing the First principle calculation method.
Keywords: cohesive energy, lattice parameter, nanocrystals, molecular dynamics